Basketball-Based Learning: An Innovative Method in English Language Learning in Elementary Schools - Hita, I Putu Agus Dharma; Fatmawan, Aditya Ridho (Universitas Pattimura, 2025)
English language learning in elementary schools often faces challenges in enhancing student engagement and learning effectiveness. This study aims to develop and analyze the effectiveness of the Basketball-Based Learning (BBL) method in English language learning as an innovative approach that integrates physical activity with language skill reinforcement. The research method used is classroom action research (CAR) with both qualitative and quantitative approaches. The research subjects are elementary school students who participated in the BBL intervention over several sessions. Data collection was conducted through observations, interviews, and learning outcome tests to measure students’ language skill development. The results indicate that the BBL method enhances motivation, active engagement, and comprehension of vocabulary and sentence structures in English. Game-based activities in BBL create an interactive and enjoyable learning environment, reducing students’ anxiety in using a foreign language. These findings introduce novelty in language learning by simultaneously combining cognitive and physical aspects, offering an alternative to conventional, more passive methods. This study recommends the implementation of BBL as an innovative teaching strategy in elementary schools, particularly in fostering a more dynamic learning experience. Additionally, the research implications can be further explored in social sciences and humanities studies concerning physical activity-based learning methods as a holistic approach in primary education.